A STOCHASTIC FRONTIER ANALYSIS OF UKRAINIAN BANKS EFFICIENCY - Bohdan Kyshakevych; Dmytro Mazharov (Scientific Journal of Polonia University, 2018)
The authors have developed a model for assessing the Ukrainian banks cost efficiency by means of Stochastic Frontier Analysis, in which the banks are considered as financial intermediaries. On the basis of the likelihood ratio test results the trans-logarithmic function steps forward in the role of the bank’s cost function. In the role of input variables we used the value of fixed assets, the price of labor and price of loanable fund, in the role of output − total loans, other assets and total cost.